Allocation of Opportunities to Participate in Clinical Trials during the Covid‐19 Pandemic and Other Public Health Emergencies. Issue 1 (15th December 2021) - Spector‐Bagdady, Kayte; Lynch, Holly Fernandez; Bierer, Barbara E.; Gelinas, Luke; Hull, Sara Chandros; Magnus, David; Meyer, Michelle N.; Sharp, Richard R.; Sugarman, Jeremy; Wilfond, Benjamin S.; Yearby, Ruqaiijah; Mohapatra, Seema
Abstract: Covid‐19 raised many novel ethical issues including regarding the allocation of opportunities to participate in clinical trials during a public health emergency. In this article, we explore how hospitals that have a scarcity of trial opportunities, either overall or in a specific trial, can equitably allocate those opportunities in the context of an urgent medical need with limited therapeutic interventions. We assess the three main approaches to allocating trial opportunities discussed in the literature: patient choice, physician referral, and randomization/lottery. As, we argue, none of the three typical approaches are ethically ideal for allocating trial opportunities in the pandemic context, many hospitals have instead implemented hybrid solutions. We offer practical guidance to support those continuing to face these challenges, and we analyze options for the future .